Recent advances in the extrusion methods for ceramics. Issue 1 (October 2021) - Buj, I; Vidal, D; Tejo, A; Fenollosa, F; Mesbahi, J El; Mesbahi, A El
Abstract: In recent years, extrusion 3D printing processes have undergone an important development. They allow obtaining complex shapes in an easy way and relatively low cost. Different plastic materials can be 3D printed with the fused filament fabrication (FFF) technology. Bioinert ceramics such as alumina or zirconia have excellent physical and mechanical properties (high melting point, high strength…) that make them appropriate in different fields: medicine, electronics, etc. However, 3D printing of ceramics is by far less developed than 3D printing of plastics or metals. A possible application for 3D printing of ceramics is the manufacture of prostheses, which usually have complex shapes with porous structures. Ceramic prostheses have several advantages over the use of other materials: they generate low debris, they are hard and they are inert and corrosion-resistant. In the present work the recent advances about extrusion 3D printing of ceramic materials are presented, with a special focus on the manufacture of prostheses.